Dietetic Sweet Boondi: A Sugar-Free Innovation with Stevia and Polyols - Hit J. Prajapati; Govind P. Tagalpallewar; Akashamrut M. Patel; Ramesh B. Modi; Kedar S. Damle (Archives of Current Research International, 2024)
This study successfully developed a dietetic version of sweet Boondi by replacing traditional sugar syrup with a balanced blend of natural sweeteners, including stevia and polyols like mannitol, maltitol, sorbitol, and fructooligosaccharides (FOS). Through a detailed market survey and sensory analysis of the market sweet Boondi samples, the Boondi making process was adopted and on that basis of that process dietetic sweet Boondi was made, in which the syrup made with the proportion consisting of mannitol (22 g), maltitol (16 g), sorbitol (22 g), FOS (15 g), and stevia (0.082 g) per 100 g of syrup, emerged as the most favorable formulation. This combination achieved high scores across all sensory attributes scores with colour and appearance score (7.59 ± 0.09), body and texture score (7.41 ± 0.09), flavour and taste score (7.47 ± 0.10) and overall acceptability score (7.53 ± 0.10). The findings underscore the importance of balancing polyol ratios to optimize sensory qualities, addressing consumer demand for healthier sweet without compromising on sensory attributes. This research provides a promising framework for developing dietetic versions of other traditional Indian sweets, paving the way for healthier options in the market.